PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP HASIL BELAJAR MATEMATIKASISWA KELAS V DI SD NEGERI 060903 MEDAN HELVETIA - Siregar, Hartaty Anna; Regina Sipayung; Irmina Pinem; Darinda Sofia Tanjung; Eka Margaretha Sinaga; Patri Janson Silaban (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Think Pair Share learning model on the mathematics learning outcomes of fifth-grade students at SD 060903 Medan Helvetia in the 2024/2025 academic year. The research method used is a quantitative approach with a One Group Pretest-Posttest experimental design. The research subjects were all 32 students in the fifth grade. Data collection was conducted through tests that had been validated for reliability and validity. The pretest results showed an average score of 50.31, categorized as needing improvement, while the posttest results increased to 76.09, categorized as progressing. The Pearson correlation test showed a calculated coefficient value of r = 0.777 ≥ r table = 0.349, indicating a strong correlation, with a significance level of 0.001. This means there is a very strong positive relationship between the application of the Think Pair Share model and students’ mathematics learning outcomes. Furthermore, the hypothesis test using the t-test yielded a value of t = 6.760 ≥ t table = 1.697, indicating a significant influence of the Think Pair Share cooperative learning model on students' mathematics learning outcomes.